The impact of the economic and financial crisis on the agri-food sector in Poland - Wigier, Marek; Zbigniew, Floriańczyk (Economics of Agriculture, 2010)
The global crisis affected Poland, putting its economic growth in jeopardy. This impact is reflected in deteriorated GDP growth prospects, reduced lending activity, limited access to external financing. Thus, the global crisis has become the key reason for the economic slowdown observed in Poland since mid-2008. Objective of this paper is to analyze the influence of economic crisis on the economic situation in agriculture and food industry in Poland.